Penerapan Nilai-nilai Karakter Budaya Papua dalam Pembelajaran Pendidikan Kewarganegaraan - Onnie Lumintang; Martina Kekri (Jurnal Kabar Masyarakat, 2023)
This journal discusses the implementation of character values of Papuan culture in civic education learning. By integrating various local values into the curriculum, and it is expected that learners can understand and appreciate their own culture while strengthening their civic identity. strengthen civic identity. This research uses a qualitative method qualitative method with a case study approach with the aim of exploring the impact of implementing Papuan cultural Papuan cultural character values in learning. Results show that integration of local values contributes positively to the development of students' character development and their understanding of citizenship.